Functional organotypic human lymph node model with native immune cells benefits from fibroblastic reticular cell enrichment - Andrew I. Morrison; Jesse E. Kuipers; Henk P. Roest; Luc J. W. van der Laan; Charlotte M. de Winde; Jasper J. Koning; Susan Gibbs; Reina E. Mebius (Scientific Reports)
Abstract Lymphoid organ function depends on fibroblastic reticular cells (FRCs), the non-hematopoietic mesenchymal stromal cells that crucially support immune activity in human lymph nodes (LNs). The in vitro study of human immunology requires physiological LN models, yet the inclusion of FRCs in current models is lacking. Here, we created an organotypic LN hydrogel model, containing native immune cells from LN tissue and ex vivo cultured autologous FRCs. During a oneweek culture period, enrichment of FRCs into the LN model benefited the viability of all immune cell populations, particularly B cells, and promoted the presence of certain subsets including CD4+ naïve T cells and unswitched (US) memory B cells. FRCs enhanced the production of immune-related cytokines and chemokines, such as B cell activating factor from the TNF family (BAFF), CXC motif chemokine ligand 12 (CXCL12), CC motif chemokine ligand 19 (CCL19) and interleukin-6 (IL-6). Functionality of the LN model was assessed through T cell activation by CD3 stimulation or initiation of an allogenic reaction with different maturation statuses of monocyte-derived dendritic cells (moDCs). Interestingly, T cell expansion was restricted in FRC-enriched LN models, reflecting an intrinsic characteristic of LN FRCs. As such, this organotypic LN model highlights the influence of FRCs on immune cells and allows an opportunity to further study antigen-induced immune responses, e.g. vaccine or immunotherapy testing.